2017
DOI: 10.1177/1753425917707026
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the pro-inflammatory cytokine response to endotoxin unfold in vivo but not ex vivo in healthy humans

Abstract: Clinical data indicate that inflammatory responses differ across sexes, but the mechanisms remain elusive. Herein, we assessed in vivo and ex vivo cytokine responses to bacterial endotoxin in healthy men and women to elucidate the role of systemic and cellular factors underlying sex differences in inflammatory responses. Participants received an i.v. injection of low-dose endotoxin (0.4 ng/kg body mass), and plasma TNF-α and IL-6 responses were analyzed over a period of 6 h. In parallel, ex vivo cytokine produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…Interestingly, such as with depression [43], there is some evidence for sex differences in the inflammatory and behavioral responses to experimental endotoxemia [44], but so far the findings are inconsistent. Some studies found a heighted pro-inflammatory response and more pronounced mood disturbances after LPS administration in women compared to men, while others did not [45][46][47][48][49][50]. It is possible that this heterogeneity is related to the hormonal status of the female volunteers, but this needs to be confirmed in future studies.…”
Section: Endotoxin-induced Inflammation: Effects On Mood and Behaviormentioning
confidence: 99%
“…Interestingly, such as with depression [43], there is some evidence for sex differences in the inflammatory and behavioral responses to experimental endotoxemia [44], but so far the findings are inconsistent. Some studies found a heighted pro-inflammatory response and more pronounced mood disturbances after LPS administration in women compared to men, while others did not [45][46][47][48][49][50]. It is possible that this heterogeneity is related to the hormonal status of the female volunteers, but this needs to be confirmed in future studies.…”
Section: Endotoxin-induced Inflammation: Effects On Mood and Behaviormentioning
confidence: 99%
“…In contrast to other studies, the authors found no significant differences when looking at sex and inflammatory markers in relation to adipose tissue. In another study aimed at elucidating mechanisms responsible for differences in inflammatory responses across sexes, Wegner et al found that proinflammatory responses to endotoxin in women were greater compared to Sex Differences in Obesity-Induced Inflammation DOI: http://dx.doi.org/10.5772/intechopen.84941 men, with significantly higher increases in plasma TNF-alpha and IL-6 [32]. Interestingly, increases in circulating plasma cortisol levels were also found to be significantly elevated in women as compared to men, which could play a role in the heightened response.…”
Section: Gender-specific Differences In Aging Due To Inflammationmentioning
confidence: 99%
“…Another limitation was the use of a mixed-gender population for the ex vivo model in comparison to an all-male population in vivo, which might influence the differences observed in immune response between the two models. Wegner et al observed a higher pro-inflammatory cytokine response to LPS in females compared to males, which was significant only in vivo but not ex vivo 36 . Nonetheless, we performed a preliminary analysis on the healthy volunteers population (n = 180) in the REALISM project 37 and so far we didn't observe a significant gender-related difference for the transcriptomic markers included in the IPP tool (unpublished data).…”
Section: Discussionmentioning
confidence: 93%